Use of frontal flap for reconstruction of malar region following arteriovenous malformation resection: a case report - Olvera Yarza, Francisco A.; Pallares, Fernando Téllez; Lara Mejía, Aldo; Yarza, Miguel Jiménez; Guzmán, Enrique E. Pérez (International Journal of Research in Medical Sciences, 2023)
Arteriovenous malformations (AVMs) are rare congenital vascular anomalies characterized by abnormal artery-vein connections. These malformations often occur intracranially but can be found in extracranial regions, presenting unique clinical challenges. Diagnosis and staging, typically using the Schobinger clinical classification, are essential, and various imaging techniques aid in the process. Treatment of AVMs is a multidisciplinary effort, with minimally invasive endovascular procedures being preferred, and surgical resection considered for extensive cases. In this case report, a 52-year-old male with an AVM in the malar region underwent successful treatment. The procedure involved preoperative marking, anesthesia, flap division, AVM resection, and flap placement, followed by suturing and a second surgical stage. The successful utilization of a contralateral frontal flap for reconstruction following AVM resection is highlighted. This case underscores the importance of a multi-stage surgical approach and careful flap preservation in AVM treatment, emphasizing the skills of surgeons. Collaboration among various medical specialties is crucial for effectively managing AVMs, combining embolization, resection, and reconstruction for tailored treatment that improves both function and aesthetics.